Verbascoside Protects Pancreatic β-Cells against ER-Stress - Galli, Alessandra; Marciani, Paola; Marku, Algerta; Ghislanzoni, Silvia; Bertuzzi, Federico; Rossi, Raffaella; Di Giancamillo, Alessia; Castagna, Michela; Perego, Carla (Biomedicines, 2020)
Substantial epidemiological evidence indicates that a diet rich in polyphenols protects against developing type 2 diabetes. The phenylethanoid glycoside verbascoside/acteoside, a widespread polyphenolic plant compound, has several biological properties including strong antioxidant, anti-inflammatory and neuroprotective activities. The aim of this research was to test the possible effects of verbascoside on pancreatic β-cells, a target never tested before. Mouse and human β-cells were incubated with verbascoside (0.8–16 µM) for up to five days and a combination of biochemical and imaging techniques were used to assess the β-cell survival and function under normal or endoplasmic reticulum (ER)-stress inducing conditions. We found a dose-dependent protective effect of verbascoside against oxidative stress in clonal and human β-cells. Mechanistic studies revealed that the polyphenol protects β-cells against ER-stress mediated dysfunctions, modulating the activation of the protein kinase RNA-like endoplasmic reticulum kinase (PERK) branch of the unfolded protein response and promoting mitochondrial dynamics. As a result, increased viability, mitochondrial function and insulin content were detected in these cells. These studies provide the evidence that verbascoside boosts the ability of β-cells to cope with ER-stress, an important contributor of β-cell dysfunction and failure in diabetic conditions and support the therapeutic potential of verbascoside in diabetes.